Carbon composite membranes for thermal-driven membrane processes. (July 2021) - Yuan, Ziwen; Yu, Yanxi; Sui, Xiao; Yao, Yuanyuan; Chen, Yuan
Abstract: Thermal-driven membrane processes, including membrane distillation (MD) and pervaporation (PV), are promising for various applications. However, they are currently hindered by low productivity, poor long-term stability, and low energy efficiency. Carbon materials, such as activated carbon, carbon black, graphite, carbon nanotubes, and graphene, offer tunable structures and surface functional groups, high mechanical/thermal stability, electrical conductivity, and excellent photothermal properties. They enable novel carbon composite membranes to address the problems of MD and PV. This review summarizes the latest research in developing carbon composite membranes for MD and PV. Membrane properties desirable in MD and PV are first analyzed, followed by reviewing different membrane fabrication methods. Representative studies on applying carbon composite membranes in MD and PV to enhance their performance and stability, create antifouling properties, and mitigate the trade-off between permeability and selectivity are discussed together with analyses of their mechanisms. Two new MD processes ( i.e., interfacial heating MD and electrically assisted MD) enabled by carbon materials are also highlighted. Last, we provide our perspectives on future research in this emerging research area. We hope that this review will inspire future endeavors to develop advanced carbon composite membranes for realizing more practical applications of thermal-driven membrane processes. Graphical abstract: Image 1